Tinjauan Hukum Islam Terkait Pelaksanaan Akad Nikah Secara Virtual - lestari, arum ayu; Arifin, Mochammad (Universitas Nahdlatul Ulama Blitar, 2023)
Ijab and qabul become one of the shamans who must get more attention. Ijab and qabul are required to be carried out in one mejelis/place. It will be a problem when ijab and qabul are carried out virtually in the event of conditions that do not support the covid-19. it affects the validity of marriage. The method used by the author uses a normative method, whose analysis is based on regulations and also the Library study. Researchers aim to know the validity of marriages that are carried out virtually. The results of this study, the researcher found that at the time of the pronunciation of the qabul when the bride and groom was not in one place, then the bridegroom must appoint a representative to represent himself carrying out the ijab and qabul. If there really isn't anyone in this world who wants to represent, then he can do the virtual qabul